Drought Tolerance in Plants: Physiological and Molecular Responses - Mostafa Haghpanah; Seyyedhamidreza Hashemipetroudi; Ahmad Arzani; Fabrizio Araniti (Plants)
Drought, a significant environmental challenge, presents a substantial risk to worldwide agriculture and the security of food supplies. In response, plants can perceive stimuli from their environment and activate defense pathways via various modulating networks to cope with stress. Drought tolerance, a multifaceted attribute, can be dissected into distinct contributing mechanisms and factors. Osmotic stress, dehydration stress, dysfunction of plasma and endosome membranes, loss of cellular turgidity, inhibition of metabolite synthesis, cellular energy depletion, impaired chloroplast function, and oxidative stress are among the most critical consequences of drought on plant cells. Understanding the intricate interplay of these physiological and molecular responses provides insights into the adaptive strategies plants employ to navigate through drought stress. Plant cells express various mechanisms to withstand and reverse the cellular effects of drought stress. These mechanisms include osmotic adjustment to preserve cellular turgor, synthesis of protective proteins like dehydrins, and triggering antioxidant systems to counterbalance oxidative stress. A better understanding of drought tolerance is crucial for devising specific methods to improve crop resilience and promote sustainable agricultural practices in environments with limited water resources. This review explores the physiological and molecular responses employed by plants to address the challenges of drought stress.